Magnetic Mechanoactivation of Wnt Signaling Augments Dopaminergic Differentiation of Neuronal Cells. Issue 9 (19th August 2019) - Rotherham, Michael; Nahar, Tasmin; Goodman, Timothy; Telling, Neil; Gates, Monte; El Haj, Alicia
Abstract: Wnt signaling is a key developmental pathway that regulates dopaminergic progenitor cell proliferation and differentiation during neuronal development. This makes Wnt signaling an important therapeutic target for neurodegenerative conditions such as Parkinson's disease. Wnt signaling can be modulated using peptides such as UM206, which bind to the Wnt receptor Frizzled. Previous work has demonstrated remote activation of the Wnt pathway through Frizzled using peptide‐functionalized magnetic nanoparticles (MNPs) with magnetic field stimulation. Using this technology, Wnt signaling is remotely activated in the neuronal cell line SH‐SY5Y, and the phenotypic response to stimulation is assessed. Results indicate β‐catenin translocalization and activation of TCF/LEF responsive transcription in response to MNP and magnetic fields, which result in dopaminergic marker expression when synergistically combined with differentiation factors retinoic acid and the phorbol ester phorbol 12‐myristate 13‐acetate. This approach is translated into ex vivo postnatal rat brain slices modeling the developing nigrostriatal pathway. Dopaminergic marker expression is maintained in MNP‐labeled SH‐SY5Y cells after injection and magnetic stimulation. These results demonstrate the translational value of remote control of signal transduction for controlling neuronal precursor cell behavior and highlight the potential applications for controlled cell differentiation as part of cell therapies for neurodegenerative disease. Abstract : Magnetic nanoparticles are functionalized with peptides and used to target the Wnt pathway receptor Frizzled at the cell surface. A magnetic force bioreactor is then used to remotely activate the Wnt pathway in SH‐SY5Y cells. This is shown to augment dopaminergic differentiation of SH‐SY5Y cells in vitro and ex vivo in organotypic brain slices from embryonic rats.